252 HETEROGENEITY OF CLINICAL LYMPH NODE INVOLVEMENT (CN+) IN ESOPHAGEAL CANCER: A PERSPECTIVE BASED ON METABOLIC VOLUME. (14th September 2020) - Lin, D; Liu, G; Tan, L
Abstract:  : Esophageal cancer with clinical lymph node involvement (cN+) is a heterogeneous disease. Although the cN+ category is of vital importance, preclinical staging cannot establish the number of positive nodes. In this study, we aimed to measure the heterogeneity of esophageal cancer with cN+ based on metabolic volume. We investigated its influence on the response to neoadjuvant treatment. Methods: We retrospectively reviewed the patients received neoadjuvant chemotherapy (nCT) and neoadjuvant chemoradiotherapy (nCRT) followed by esophagectomy during January 2016 and November 2018. All patients had received baseline 18F-FDG PET/CT. All patients were restaged according to the 8th TNM Staging System. We measured the metabolic tumor volume (MTV, cm3) of the whole body (MTVwb) and the primary tumor (MTVp) on the workstation. We also calculated the difference of MTVwb and MTVp (MTVn) and the ratio of MTVwb and MTVp (MTVratio). Logistic regression was used to determine the association between the heterogeneity and the response to neoadjuvant treatment. Results: Among the 102 patients enrolled in this study, 54 patients had clinically suspicious lymph nodes in small diameters with lower uptake (MTVn as 0). The median MTVwb, MTVp, and MTVn of the patients were 22.34 (2.09 to 105.24), 19.62 (1.93 to 98.06), and 0 (0 to 89.00), respectively. In nCT and nCRT groups (all patients), 15 (37.5%) and 38 (61.3%) achieved ypN0, respectively. In nCT and nCRT groups (MTVn as 0), 12 (42.9%) and 20 (76.9%) patients achieved ypN0, respectively. Logistic regression revealed that MTVn (0 vs. >0) was independently associated with ypN status in nCRT group (P = 0.035). Conclusion: nCRT compared with nCT achieved more effective disease control. In esophageal cancer treated with nCRT, the heterogeneity of cN+ measured by metabolic volume was associated with ypN status. A prospective study was in demand to further validate the findings. Video: none